Evaluation of quality of kidneys from donation after circulatory death/expanded criteria donors by parameters of machine perfusion. Issue 2 (18th January 2018) - Chen, Guodong; Wang, Chang; Zhao, Yi; Qiu, Longhui; Yuan, Xiaopeng; Qiu, Jiang; Wang, Changxi; He, Xiaoshun; Chen, Lizhong
Abstract: Aim: To investigate whether the parameters of machine perfusion could predict the quality of kidneys from donation after circulatory death (DCD) donors and expanded criteria donors (ECD). Methods: Fifty‐eight kidneys from DCD/ECD donors were harvested in our hospital from July 2011 to August 2014. All kidneys were preserved with machine perfusion (Life Port), and parameters of machine perfusion were collected. All kidneys were biopsied before transplantation. The primary endpoints were delayed graft function (DGF), graft loss and patient death. Results: After kidney transplantation, 26 patients (44.8%) had DGF. We chose 1 h RI as a predictive parameter to predict DGF after transplant, and made the ROC curve. The ROC curve showed that 1 h RI = 0.4 was the best cut‐off point for predicting DGF after transplant. The sensitivity was 61.54%, and the specificity was 81.25%. Fifty‐eight recipients were divided into two groups according to 1 h RI of machine perfusion. 22 cases in high RI group (RI > 0.4) and 36 cases in low RI group (RI ≤0.4). DGF rate was significantly higher in the high RI group (72.7% vs. 27.8%). One year serum creatinine levels were also significantly higher in the high RI group ( P < 0.05). Acute rejection rate and 1 year graft and patient survival were comparable. Conclusions: One hour RI of machine perfusion is associated with DGF and 1 year graft function in DCD/ECD kidney transplantation, and may be a non‐invasive tool for evaluating quality of DCD/ECD kidneys. Summary at a Glance: In this paper the Resistive Index of DCD/ECD kidneys at 1 h post‐perfusion was found to associate with risk of delayed graft function suggesting that this could be a useful marker for predicting DGF in machine perfused kidneys.